TGF-beta coordinately activates TAK1/MEK/AKT/NFkB and SMAD pathways to promote osteoclast survival. - Gingery, A; Bradley, E; Pederson, L; Ruan, M; Horwood, N; Oursler, M (2008)
To better understand the roles of TGF-beta in bone metabolism, we investigated osteoclast survival in response TGF-beta and found that TGF-beta inhibited apoptosis. We examined the receptors involved in promotion of osteoclast survival and found that the canonical TGF-beta receptor complex is involved in the survival response. The upstream MEK kinase TAK1 was rapidly activated following TGF-beta treatment. Since osteoclast survival involves MEK, AKT, and NFkappaB activation, we examined TGF-beta effects on activation of these pathways and observed rapid phosphorylation of MEK, AKT, IKK, IkappaB, and NFkappaB. The timing of activation coincided with SMAD activation and dominant negative SMAD expression did not inhibit NFkappaB activation, indicating that kinase pathway activation is independent of SMAD signaling. Inhibition of TAK1, MEK, AKT, NIK, IKK, or NFkappaB repressed TGF-beta-mediated osteoclast survival. Adenoviral-mediated TAK1 or MEK inhibition eliminated TGF-beta-mediated kinase pathway activation and constitutively active AKT expression overcame apoptosis induction following MEK inhibition. TAK1/MEK activation induces pro-survival BclX(L) expression and TAK1/MEK and SMAD pathway activation induces pro-survival Mcl-1 expression. These data show that TGF-beta-induced NFkappaB activation is through TAK1/MEK-mediated AKT activation, which is essential for TGF-beta to support of osteoclast survival.